KAJIAN PERKEMBANGAN PEMIKIRAN MANAJEMEN: GERAKAN PEMIKIRAN SCIENTIFIC MANAGEMENT HINGGA KAIZEN - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2017)
This article is a summary of the various ideas related to the concepts and techniques of management of the industrial revolution to the modern era. The research method used was a review of the literature related to management thinking. In this article the various movements of thought are grouped into four areas of thought or theory. The division is not based on the periodicity of the year, but more to the realm of thought developed. The fourth field is the thought of Scientific & administrative management theory, behavioral management theory, quantitative management theory and modern management theory and Kaizen. Field of thought is presented based on the appearance of the field earlier than other areas of thought, even in the era of the movement of thought or one area may also appear a work that is part of another movement of thought. The results of the literature review of this study show that the development of management thought started thinking mechanically related and productivity in manufacturing, and then evolved to the related study of human nature and behavior and proceed to the field of the relationship between humans and system organization. This study also found a lack of attention from historians related to the development of management thought management business focusing on marketing or customer oriented.